"Unity in Diversity": A Conversation around the Interdisciplinary Identity of Information Science. Issue 1 (13th October 2021) - Rorissa, Abebe; Iyer, Hemalata; Albright, Kendra; Potnis, Devendra; Caidi, Nadia; Alemneh, Daniel
Abstract: As a dynamic and interdisciplinary field of study, information science has a diverse set of methods, theoretical frameworks, tools and processes that continue to be developed, adopted, and extended through further research, teaching, and practice. Some of the methods and frameworks have origins in other disciplines. The interdisciplinary nature of information science may have enabled the field to grow in stature but it may have also contributed to it being perceived, often unfairly and mistakenly, as lacking a strong identity, brand, and reputation, leading to a possible fragmentation of the field. Continued conversations around factors that may help and/or hinder the field from fulfilling its full potential and how it can position itself to build an identity on a strong track record are necessary. The panel has two main goals: (1) to engage researchers and educators in an interactive discussion on the contributing factors and ways in which information science can remain a diverse and interdisciplinary field, realize its full potential, and build a strong identity as well as identify potential barriers it needs to overcome; and (2) to delineate the roles its stakeholders and allies need to play to achieve that goal of a field with "Unity in diversity".